Interaction Between Ator and Fennel in the Treatment of Obesity in Rats - El ghazaly NA; Radwan EH; H. Zaatout Hala; M Elghazaly Mohamed; Eldien Allam Nour (Journal of Obesity Management, 2019)
Obesity can be defined as a condition of abnormal or excess fat accumulation in adipose tissue, to the extent that health may be impaired. Fennel is one of the oldest spice plants which widely grows in arid and semi-arid and due to its economic importance and pharmaceutical industry usage. This plant has anti-inflammatory and analgesic effect and is effective in gastrointestinal disorder treatment. The aim of the present study was to evaluate the phytochemical characteristics and therapeutic properties of this medicinal plant. The current study demonstrates that the alteration induced by high fat diet causing changes in blood parameters. These changes are exhibited through a decrease in RBCs, Ht, Hb and platelet and these changes could be due to oxidative stress, which lead to lipid peroxidation in RBCs membranes, auto oxidation of hemoglobin. As regards the total WBCs, lymphocytes and monocytes showed marked decrease. While a distinct increase in the percentage of neutrophils and eosinophil. The present, demonstrates that rats treated with (fennel), (ator) and (fennel with ator) exposure provided significant protection to the altered hematological variables. The effect of the treatment with fennel and ator more effect than fennel only and ator only. The finding of this study indicates that the concentration of Malondialdehyde (MDA) and Myeloperoxidase (MPO) in liver homogenates of the fennel and ator group significant decrease than group (3) and group (4) and the obese group. There is a growing awareness that obesity is a prime risk factor for the development of dyslipidemia profile and that oxidative stress may play a role in various adverse effects of obesity.
Keywords: Ator